PENERAPAN PENDEKATAN PENGAJARAN TERBALIK UNTUK MENINGKATKAN HASIL BELAJAR SAINS SISWA KELAS V SDN 008 PENDALIAN KECAMATAN PENDALIAN IV KOTO KABUPATEN ROKAN HULU - Liluk Sriwulan Rohmadoni (JURNAL PAJAR (Pendidikan dan Pengajaran), 2017)
This research is motivated by the low learning outcomes of students in grade V at the SDN 008 PendalianKecamatan Pendalian IV Koto Kabupaten Rokan Hulu. This study aims to improve the learning outcomes ofscience students of grade V SDN 008 Pendalian Kecamatan Pendalian IV Koto Kabupaten Rokan Hulu with theapplication of reverse teaching approach, which is implemented for 1 month. The subjects of this study arestudents of class V SDN 008 Pendalian Kecamatan Pendalian IV Koto Kabupaten Rokan Hulu which amountedto 21 people of the academic year 2016-2017. The form of research is classroom action research. The instrumentof this research consisted of performance instrument and data collection instrument in the form of observationsheet of teacher activity and student activity. Based on the results of research that has been done, known studentlearning completeness increased by (43% in preliminary data, 67% in cycle I and 86% in cycle II). So theincrease from the initial data, cycle I and cycle II is 43%. Thus the hypothesis of action on this research that isInverse teaching approach can increase results learning science materials human respiratory organs studentsclass V SDN 008 Pendalian Kecamatan Pendalian IV Koto Kabupaten Rokan Hulu "acceptable".